Evidence of functional deficits at the single muscle fiber level in experimentally-induced renal insufficiency. (3rd January 2019) - Mitrou, Georgia I.; Sakkas, Giorgos K.; Poulianiti, Konstantina P.; Karioti, Aggeliki; Tepetes, Konstantinos; Christodoulidis, Grigorios; Giakas, Giannis; Stefanidis, Ioannis; Geeves, Michael A.; Koutedakis, Yiannis; Karatzaferi, Christina
Abstract: Chronic kidney disease patients present with metabolic and functional muscle abnormalities, called uremic myopathy, whose mechanisms have not yet been fully elucidated. We investigated whether chronic renal insufficiency (CRI) affects skeletal muscle contractile properties at the cellular level. CRI was induced surgically in New Zealand rabbits (UREM), with sham-operation for controls (CON), and samples were collected at 3 months post-surgery, following euthanasia. All protocols had University Ethics approval following national and European guidelines. Sample treatments and evaluations were blinded. Maximal isometric force was assessed in 382 permeabilized psoas fibers (CON, n = 142, UREM, n = 240) initially at pH7, 10 °C ('standard' conditions), in subsets of fibers in acidic conditions (pH6.2, 10 °C) but also at near physiological temperature (pH7, 30 °C and pH6.2, 30 °C). CRI resulted in significant smaller average cross sectional areas (CSAs) by ∼11% for UREM muscle fibers (vs CON, P < 0.01). At standard conditions, UREM fibers produced lower absolute and specific forces (i.e. normalized force per fiber CSA) (vs CON, P < 0.01); force increased in 30 °C for both groups (P < 0.01), but the disparity between UREM and CON remained significant. Acidosis significantly reduced force (vs pH7, 10 °C P < 0.01), similarly in both groups (in UREM by −48% and in CON by −43%, P > 0.05). For the first time, we give evidence that CRI can induce significant impairments in single psoas muscle fibers force generation, only partly explained by fiber atrophy, thus affecting muscle mechanics at the cellular level.